Challenges to Women’s Political Participation in Makran Division of The Balochistan Province of Pakistan - Ahmed, Changiz; Ghafoor, Sidra Abdul; Ahmed, Mumtaz (Journal of Development and Social Sciences, 2024)
The paper aims to explore the relation between religion, economy, culture, and the political status of women in Makran. Makran, being a division of the Province of Balochistan located at the southwest of the province, is rich in intellect and history. The region is a conflict-ridden zone at present badly hit by the waves of Baloch insurgency. Even though the participation of women in the field of education is quite encouraging, yet they have a very meagre share in politics. Religious considerations, economic dependence on males and cultural values contribute to create problems for women to engage in political affairs. Appropriate literature is reviewed to identify the issues that act as stumbling blocks to prevent women of Makran from the exercise of their constitutional right to make their presence felt in legislation and policy making. The kind of purposive sampling is used by conducting a survey to collect data and analyze it to arrive at a workable solution of the challenges that women of the area face. However, the results of the study suggest that women of Makran have very poor performance in politics, since the entire division has only three representatives in assemblies. Women cannot make decisions independently in the presence of male dominance. Until females are economically independent their political autonomy remains an unachievable dream. Civil society, being an integral part of the triangle of the modern state needs to be vigilant in the propagation of gender equality. Policies like creation of women party caucuses and networks, more reserved seats in assemblies and affirmative actions will serve well to ensure proportional representation of women in the political process promoting democracy and sustainability.